ASTRONOMIYA MASHGʻULOTLARI SAMARADORLIGINI TARIXIY-MOLIYAVIY RAMZLARNI NAMOYISH ETISH ORQALI OSHIRISH - Saburova, G.G. (SCIENCE and SOCIETY, 2020)
The article discusses one of methods of enhancing the effectiveness of astronomy classes. In particular, a recommendation is given to use the “demonstration of historico-financial symbols” method in astronomy classes. The principle of the method is to present historical-financial symbols (or coins) that reflect the identities of the astronomers or discoveries related to them with giving a brief information about them.